Espaços e relações de poder em Chapecó/SC na década de 1950. - Cristina de Moraes (Confins)
This study aims to analyze how the valuation of certain areas was built by the power relationships established over time as well as the use of these same spaces as significant and as transmitters of values guiding social action. The main point of analysis is to understand this idea from the occurrence of a lynching in Chapecó / SC in 1950. From geographical-historical contextualization is possible to see how a particular type of training and its sociospatial social relations were embryos of power relations that gradually have taken root in the region, influencing the creation of ideologies that gained widespread materiality. From the establishment of the colonies migration in the mid-twentieth century, new actors have emerged and have been inserted in the power relations established previously, with the process of re-articulation between the new and old to unit maintained an already established order. Later with the consolidation of these colonies migration Chapecó became an attractor of population, resulting in the arrival of new migrants. Inserted in the emergence of the new multipartidarimo Brazilian, new actors created a political party linked to the urban and liberal professional activities, representing a break with traditional power groups, and this opposition got clear expressiveness when the latter lost the municipal elections in October 1950. In parallel, several fires happened and burning the church had great impact on the local society, because the population had in religion one of its core values and element of local identity, feeling so disrespected. The church fire was used to incriminate individual of the urban / liberal party in this crime, with the aim of intimidating people who were not inserted into the traditional power relations, and the suspects were arrested and subsequently lynched. In this lynching is possible to see that places very important for the local society were used strategically, enabling to reinforce traditional social values when the strength of these spaces as transmitters of values were highlighted by local groups. One can see that the spaces are not only a condition of existence, is also a social construction, loaded with meanings, values aimed at inculcating ideas and guide behaviors.